Trends in the Clinical Pattern, Diagnosis and Management of Rhinosinusitis in a Sub-urban Tertiary Health Centre - Sogebi OA; Oyewole EA (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2015)
Background: Rhinosinusitis (RSS) is a common form of upper airway disease encountered by Otolaryngologists. Objectives: To describe the trends in the clinical presentation, diagnosis and management of RSS in a tertiary hospital. Methods: Retrospective analysis of clinical information retrieved from the hospital records of patients with RSS managed in the ENT department of OOUTH Sagamu over an 18-month period was done. Results: Out of 1814 patients, 143 had RRS with the prevalence rate of 7.9%. The male-to-female ratio was 1.1:1, the age ranged from 7 to 79 (median = 32.4) years. The presenting symptoms included mucoid nasal discharge (68.7%), nasal congestion (61.5%) and excessive sneezing (46.8%). Most (71.3%) of the patients presented after 3weeks of the onset of symptoms and the median duration was 3.2 months. The leading physical findings included engorged nasal turbinates (78.3%), ooedematous nasal mucosa (72.0%), mucopurulent anterior rhinorrhoea (28.6%) and pale nasal mucosa (25.9%). The investigations done included plain X-Rays of the sinuses (86.0%), full blood count (67.1%) and computerized tomographic (CT) scan of the sinuses (8.4%). Plain X-Ray abnormalities were most common in the maxillary sinuses (45.5%) while 30.1% had multi-sinusitis. The trend of diagnosis ranged from infective RSS in 51.7% to allergic RSS in 38.5%. About a quarter had different forms of non-endoscopic surgical intervention. Recorded complications included nasal polyps in 11.9%. Conclusion: The trend of RSS observed relative affectation of adults and mostly chronic infective types, and sometimes allergic types. Radiological assessment was by plain X-Rays in most cases, management was either medical or non-endoscopic surgical methods, frequently complicated by polyps.